Антикризове управління інвестиційними проєктами в бізнес-плануванні підприємства під час воєнного стану - Болтянська, Лариса Олексіївна; Лисак, Оксана Іванівна; Сиротюк, Ганна Володимирівна; Boltianska, Larysa; Lysak, Oksana; Syrotyuk, Hanna (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті досліджено особливості антикризового управління інвестиційними проєктами в системі бізнес-планування підприємства в умовах воєнного стану. Обґрунтовано необхідність адаптації традиційної структури бізнес-плану до посилення ризиків, ресурсних обмежень, нестабільності фінансування та змін ринкового середовища. Проаналізовано вплив сучасних тенденцій інвестиційної активності в Україні на зміст основних розділів бізнес-плану. Запропоновано адаптовану структуру бізнес-плану інвестиційного проєкту, що передбачає поглиблений аналіз середовища, сценарне планування, розширення ризик-менеджменту, використання альтернативних джерел фінансування та постійний моніторинг реалізації проєкту. Визначено практичне значення запропонованих підходів для підвищення стійкості підприємства. /// EN: The article examines the theoretical and methodological foundations of anti-crisis management of investment projects within the enterprise business planning system under martial law. It is substantiated that the full-scale war has significantly changed the conditions for implementing investment initiatives, increased uncertainty, risk, and resource constraints, which necessitates a revision of traditional approaches to business plan development. It is determined that, under current conditions, a business plan should perform not only the function of economic substantiation of a project, but also the role of a tool for coordinating anti-crisis actions, risk management, ensuring financial stability, and adapting the project to changes in the external environment. Scientific approaches to the interpretation of business planning, project management, risk management, and business resilience are generalized. It is established that existing studies do not sufficiently cover the integration of anti-crisis mechanisms into the structure of an investment project business plan throughout its entire life cycle. The impact of structural changes in investment activity in Ukraine on the content of individual sections of the business plan is analyzed. It is proved that the predominance of investments in tangible assets, the dominance of internal sources of financing, the declining role of loans and borrowings, the limited participation of foreign investors, the growing role of public financing, and the intensification of wartime risks change the requirements for the preparatory, marketing, production, organizational, financial, and risk-related sections of the business plan. An adapted structure of the investment project business plan is proposed, which предусматривает strengthening the analytical block, expanding the risk management system, applying scenario planning, reserving resources, using alternative sources of financing, and introducing continuous monitoring of project implementation. A conceptual model for adapting the business plan structure to martial law conditions has been developed. The practical value of the results lies in the possibility of using the proposed provisions to improve the validity of investment decisions. It is substantiated that the anti-crisis modification of a business plan increases the realism of managerial decisions, controllability, flexibility, and financial stability of an investment project, as well as the enterprise’s ability to respond to external shocks.
Anti-crisis management of investment projects in enterprise business planning during martial law
Keywords: антикризове управління; інвестиційний проєкт; бізнес-планування; воєнний стан; ризик- менеджмент; фінансова стійкість; адаптація; підприємство; інвестиції; anti-crisis management; investment project; business planning; martial law; risk management; financial stability; adaptation; enterprise; investments